Анализатор потребления кислорода - Гиренко, Л.Л. (Вестник зоологии, 1967)
A new design provides the stable temperature conditions of the experiment, a number of glass units and weight of the instrument is decreased. The instrument is more compact and convenient for application. The body of the instrument is cylindrical (230X X 222 mm). Respiratory and oxygen chambers are united into one block — metal inner cylinder, which is enveloped by water jacket, connected with ultrathermostatic regulator of «TC-15» type. An inserted block, which is completely put into the respiratory chamber before the experiment, unites the cage for an animal and the vessel for the solution of NaOH which absorbs CO2. The oxygen chamber with respiratory one and the exhaust pipe of the controller of air pressure with oxygen chamber are connected correspondingly by means of three-way glass cocks that provides the quick inflation of the chamber with oxygen. In a new construction the principle of operation is preserved as well as the automatic controller of air pressure and the burette (but somewhat changed) applied by Skvortsov. Two-way glass cocks soldered in the upper end of the burette accelerate its filling with water. A bronze glass with two copper pipes, in the former the lower end of the burette being fixed, permits increasing its term of use, whereas the same glass pipes in Skvortsov's burette caused a greater fragility of the detail.